Pengaruh Konsentrasi Nutrisi AB Mix dan Waktu Pemangkasan Terhadap Pertumbuhan dan Produksi Timun Suri Hidroponik dengan DBS (Dutch Bucket System) - Endang Sri Wahyuni; Nadif Ali Wasil Laeli (Program Studi Agroteknologi, 2026)
This study aimed to determine the optimal concentration of AB Mix nutrients and the best shoot pruning time for the growth and yield of Cucumis melo L. var. reticulatus naudin (Timun Suri) cultivated using the DBS hydroponic method. The research was conducted in the Greenhouse of the Agrotechnology Study Program, Faculty of Agriculture, Islamic University of Jember. The study employed a factorial Completely Randomized Design (CRD) with a 3 × 4 factorial arrangement and three replications. Observations were carried out at 10-day intervals after planting. The first factor was the concentration of AB Mix nutrients (N), consisting of three levels: N1 = 1800 ppm, N2 = 2000 ppm, and N3 = 2200 ppm. The second factor was the timing of shoot pruning (P), consisting of three levels: P0 = no pruning, P1 = 20 days after planting (DAP), and P2 = 25 DAP. Data were analyzed using ANOVA (F-test) to determine the effect of the treatments. If a significant or highly significant difference was found, Duncan’s Multiple Range Test (DMRT) at a 5% significance level was conducted using SPSS Statistics 25 for Windows. Results showed 2000 ppm AB Mix concentration was best for the stem diameter parameter, while 2200 ppm was optimal for plant height, number of leaves, and all fruit-related parameters. No pruning produced the best results for almost all parameters except fruit length, whereas pruning at 25 days after planting (25 DAP) was best for plant height and number of leaves. The interaction between 2200 ppm AB Mix concentration and no pruning gave the best results for fruit weight, volume, diameter, circumference, and thickness.